Quality credit evaluation in the internet company: a system based on the analytic hierarchy process - Yang, Jing; Vargas, Luis G.; Jin, Xiang; Zhou, Lijun (Journal of Business Economics and Management, 2020)
Quality credit has attracted considerable interest in both academia and business world in recent years in China. This study aims to discuss the development of quality credit evaluation system, and then based on an Analytic Hierarchy Process (AHP) to construct an evaluation system for Internet companies. Firstly, the quality credit evaluation three-level pyramid model for Internet companies has been established, including the willingness of quality credit, the ability of quality credit, and the basis of quality credit.  Secondly, priorities of the criteria and sub-criteria are assigned and identified by the AHP with 12 experts those who are representatives from Internet companies, research experts, and government staffs. Finally, several US Internet companies are evaluated by using this evaluation system, and practical suggestions are provided for the future based on data evaluation results. This paper finds that in the criteria of quality credit evaluation system, the most significant indicators are credit records and quality of product, while qualification rate of product supervise, operating legitimacy and quality accident are the most primary indicators in the sub-criteria level.